Experimental investigation of single particle settling in turbulence generated by oscillating grid - Zhou, Qi. (2012)
In this study, turbulence influence on the settling behavior of solid particles was investigated experimentally in confined turbulent aquatic environment generated by oscillating grid. An enhanced PIV system was employed to conduct simultaneous velocity measurements of individual settling particles and ambient fluid. Grains varying in shape (spherical and cylindrical) and diameter (2.78-7.94 mm) were tested with different turbulent conditions.